Zinc negative electrode protective layer material of aqueous zinc ion battery as well as preparation method and application of zinc negative electrode protective layer material
By using titanium dioxide quantum dot load-launched graphite material as a protective layer in aqueous zinc ion batteries, the corrosion problem of zinc metal negative electrodes is solved, the corrosion resistance and cycle life of the battery are improved, and more efficient zinc ion deposition and battery performance are achieved.
Patent Information
- Application Number
- CN202411439752.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The corrosion problem of zinc metal negative electrode in aqueous zinc ion batteries leads to a short cycle life, hindering its stability and service life in practical applications.
Using porous composite material as the protective layer of the negative electrode of zinc ion battery, stirring the carbon material in an acidic liquid, adding manganese salt and titanium-containing organic compound, calcining to obtain titanium dioxide quantum dot-loaded expanded graphite material as a protective layer, reducing zinc Ion deposition potential energy reduces corrosion tendency and side reactions.
It significantly improves the corrosion resistance and cycle life of zinc ion batteries, improves the capacity and rate performance of the whole battery, and reduces dendritic growth, and realizes stable cycle under large, medium and small current density, and is simple in process and costly. Low, with commercial production prospects.
Smart Images

Figure CN119133356A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to a zinc ion battery negative electrode protective layer material and a preparation method thereof, and application in aqueous zinc ion battery negative electrode materials. Background Art
[0002] In recent years, industrial production and infrastructure construction have experienced rapid development, prompting people to pay more attention to the safe operation and maintenance issues in these areas. Metal materials play an important role in these production facilities and public life. With the advancement of science and technology and the improvement of living standards, people's demand for energy storage technology has also increased. Among the many electrochemical energy storage devices, lithium-ion batteries are widely used due to their advantages such as high energy density and long service life, but at the same time, they are not suitable for large-scale energy storage systems due to their high cost and many safety risks. Organic electrolytes have the advantages of low thermal stability and high conductivity, and have become the most common electrolytes in lithium-ion battery applications. However, due to the safety hazards of organic electrolytes such as flammability and toxicity, the development of batteries has been subject to certain constraints. As an environmentally friendly energy storage system, rechargeable aqueous batteries have attracted much attention due to their low cost, high safety and good durability, and have shown great application potential in many fields. In particular, aqueous zinc-ion batteries (ZIBs) have developed most rapidly, mainly due to the following reasons: (1) Zinc metal has a relatively high capacity density (5855mAh·cm -3 ) and its redox potential is comparable to that of the standard hydrogen electrode (SHE); (2) the abundant zinc resources provide a guarantee for the sustainable development of ZIBs, which are not only low in cost but also highly safe; (3) the conventional electrolyte uses a neutral or weakly acidic aqueous solution, and its conductivity (about 1S·cm -1 ) than non-aqueous electrolyte (about 1 to 10 mS·cm -1 ) is two orders of magnitude higher. However, the corrosion problem of zinc metal anode is still a key factor hindering its development, which seriously weakens the stability and service life of zinc-ion batteries in practical applications. Therefore, studying how to prevent the corrosion of zinc metal anode has great application value.
[0003] Patent CN117577766A discloses a method for preparing a zinc negative electrode protective coating for aqueous zinc ion batteries. The method uses a metal zinc negative electrode as a base and uniformly mixes sulfonated polyaniline and acrylic resin in ethanol to prepare a protective coating with both conductive and anti-corrosion functions. The metal zinc negative electrode protected by the coating has good conductivity even at a current density of 5 mA cm -2 The dough capacity is 5 mAh cm -2Under the condition of high temperature, the assembled symmetrical battery can also stably cycle for 250 hours, effectively extending the cycle life of the symmetrical battery. Patent CN117457843A discloses that a polyacrylamide polymer coating is modified on the surface of the zinc negative electrode of an aqueous zinc ion battery by a spin coating method, and the synthesized coating has a good adhesion effect. The prepared polymer coating can effectively isolate the contact between the electrode and the electrolyte and inhibit the occurrence of side reactions. In addition, the amide group exhibits a strong zinc ion adsorption capacity and can effectively regulate the uniform deposition of zinc ions. Therefore, the assembled battery achieves good cycle stability.
[0004] In order to reflect the improvement of the cycle life of aqueous zinc ion batteries by zinc-philic materials, the present invention designs a low-cost, high-safety protective layer, which effectively alleviates the problems of dendrite growth, interface corrosion, etc. Summary of the invention
[0005] In order to overcome the problems of rampant zinc negative electrode dendrite growth and short cycle life of aqueous zinc ion batteries, the present invention provides a porous aqueous zinc ion protective layer with simple process, low cost, high safety, green environmental protection and large-scale production advantages.
[0006] Another object of the present invention is to provide an application of a porous composite material in the negative electrode of an aqueous zinc ion battery, which improves the corrosion resistance, cycle life, coulombic efficiency, etc. of the symmetrical battery, and improves the capacity and rate performance of the entire battery.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] The present invention provides a method for preparing a zinc negative electrode protective layer material for an aqueous zinc ion battery, comprising the following steps:
[0009] (1) dispersing the carbon material in an acidic liquid and stirring at room temperature to fully mix the carbon material to obtain a uniform suspension;
[0010] (2) adding manganese salt to the mixed solution obtained in step (1), stirring at room temperature, and then placing in a constant temperature water bath;
[0011] (3) washing, centrifuging, drying, and calcining the product obtained by the reaction to obtain expanded graphite;
[0012] (4) uniformly dispersing the expanded graphite obtained in step (3) in a solvent, and stirring to obtain a dispersion;
[0013] (5) adding the titanium-containing organic compound to the dispersion obtained in step (4) and stirring;
[0014] (6) adding deionized water to the dispersion obtained in step (5) and refluxing;
[0015] (7) The product obtained in step (6) is centrifuged, washed, dried and calcined to obtain a protective layer.
[0016] Furthermore, in step (1), the carbon material is graphite; and the acidic liquid is 50% to 80% sulfuric acid.
[0017] Furthermore, in step (2), the manganese salt is potassium permanganate; the stirring time is 0.5-2 hours; the constant temperature water bath time is 0.5-2 hours; and the water bath temperature is 30-100°C.
[0018] Furthermore, in step (3), the washing process washes the material to neutrality; the drying time is 10-14 hours, and the drying temperature is 60-100°C;
[0019] The calcination temperature is 700-1100° C. and the calcination time is 10-60 minutes.
[0020] Furthermore, in step (4), the mass of expanded graphite added is 0.2-2 g / mL; the solvent is ethanol; and the stirring time is 0.1-1 hour.
[0021] Furthermore, in step (5), the titanium-containing organic compound is tetrabutyl titanate; the volume ratio of the titanium-containing organic compound to the ethanol dispersion is 0.5:100-1:100; and the stirring time is 0.1-1 hour.
[0022] Furthermore, the volume of the deionized water added in step (6) is 0.1:50 to 2:50 with respect to the volume of the ethanol dispersion; the reflux temperature in step (6) is 60-150° C.; and the reflux time in step (6) is 4-10 hours.
[0023] Furthermore, in step (7), the product is centrifuged 1-5 times; the drying time is 8-16 hours; the drying temperature is 60-100°C; the calcination temperature is 300-500°C; and the calcination time is 2-6 hours.
[0024] The invention provides a preparation method for preparing a protective layer of titanium dioxide quantum dots loaded with expanded graphite.
[0025] The present invention provides application of the titanium dioxide quantum dot-loaded expanded graphite material at the zinc negative electrode interface of an aqueous zinc ion battery.
[0026] Preferably, the titanium dioxide quantum dot-loaded expanded graphite material is used as a protective layer for the negative electrode of an aqueous zinc ion battery, is dissolved in NMP with conductive carbon black and a binder in a certain proportion, is slurried and coated on a zinc foil, and manganese dioxide is used as a positive electrode to form a button battery for electrochemical testing.
[0027] Furthermore, the binder is PVDF; preferably, the ratio of protective layer powder: conductive carbon black: PVDF is 7:2:1.
[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0029] 1) The present invention prepares expanded graphite by chemical oxidation, which provides a rich pore structure for zinc ion deposition, so that zinc ions can be evenly deposited on the negative electrode surface, effectively reducing the growth of dendrites.
[0030] 2) The present invention uses titanium dioxide quantum dots as zinc-philic materials, which effectively reduces the deposition potential of zinc ions, allowing zinc ions to be deposited faster, while reducing the hydrogen evolution overpotential of the zinc negative electrode, reducing the corrosion tendency of the zinc negative electrode, reducing the generation of side reactions, and improving the corrosion resistance of the zinc negative electrode.
[0031] 3) The zinc negative electrode protection strategy provided by the present invention significantly improves the cycle life of the symmetrical battery at large, medium and small current densities, and the capacity and rate performance of the full battery are also improved accordingly.
[0032] 4) The titanium dioxide quantum dots used in the present invention are loaded on the graphite material, and the loading method is simple, the process is simple, efficient, and low-cost, and the reagents used are safe and environmentally friendly, and have practical prospects for commercialization and large-scale production.
[0033] 5) The raw materials used in the present invention are widely available and the preparation methods are diverse, which provides a reference idea for people to prepare high-performance negative electrode protective layers for aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The titanium dioxide quantum dot-loaded expanded graphite (TiO 2 Scanning electron microscopy (SEM) characterization of QDs@EG).
[0035] Figure 2 The negative electrode protective layer (TiO 2 Transmission electron microscopy (TEM) characterization of QDs@EG).
[0036] Figure 3 The negative electrode protective layer (TiO 2 High-resolution transmission electron microscopy (HR-TEM) image of QDs@EG).
[0037] Figure 4The negative electrode protective layer (TiO 2 XPS spectrum of QDs@EG).
[0038] Figure 5 The negative electrode protective layer (TiO 2 QDs@EG), the negative electrode protective layer with expanded graphite obtained in Comparative Example 1, and the linear scanning voltammograms of the bare zinc electrode without the protective layer.
[0039] Figure 6 The negative electrode protective layer (TiO 2 QDs@EG), the negative electrode protective layer with expanded graphite obtained in Comparative Example 1, and the chronoamperometry diagram of the bare zinc electrode without the protective layer.
[0040] Figure 7 The negative electrode protective layer (TiO 2 QDs@EG) at a current of 5 mA cm -2 , with a capacity of 2.5 mAh cm -2 Cycling performance under .
[0041] Figure 8 The negative electrode protective layer (TiO 2 Scanning electron microscope (SEM) characterization of a symmetric battery of QDs@EG after 100 cycles.
[0042] Fig. 9 The negative electrode protective layer (TiO 2 Long cycle performance test diagram of the full battery composed of QDs@EG) and manganese oxide electrode.
[0043] Fig.10 The negative electrode protective layer (TiO 2 Self-discharge behavior of a full cell consisting of QDs@EG) and manganese oxide electrodes in electrolyte. DETAILED DESCRIPTION
[0044] The present invention is further described below in conjunction with examples, comparative examples and accompanying drawings, but the embodiments of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.
[0045] Example 1
[0046] This embodiment provides a negative electrode protective layer (TiO 2 A method for preparing QDs@EG) comprising the following steps:
[0047] (1) Add 1 g of graphite into a beaker, and then add 8 mL of 75% sulfuric acid into the beaker. Cover the dispersion with a layer of plastic wrap and stir at room temperature for 30 min. The solution is named solution (1).
[0048] (2) 0.5 g of potassium permanganate was slowly added to solution (1), followed by a constant temperature water bath at 45°C. After the reaction for one hour, the resulting material was neutralized and placed in an oven at 80°C for drying for 12 hours.
[0049] (3) The dried product obtained in step (2) is placed in a porcelain boat, and placed in a muffle furnace at 900° C. for 30 min to obtain the final product, expanded graphite (EG).
[0050] (4) 0.5 g of the synthesized expanded graphite (EG) was placed in 100 mL of ethanol and subjected to ultrasonic treatment for 30 min. 1.25 mL of tetrabutyl titanate was added to the resulting suspension and stirred for 30 min. After the stirring, 1.25 mL of deionized water was added and the resulting suspension was refluxed at 100 °C for 6 h.
[0051] (5) The obtained product was washed alternately with ethanol and deionized water for three times, dried in an oven at 80°C for 12 h, and then calcined at 400°C for 4 h in an Ar atmosphere to obtain a titanium dioxide quantum dot-loaded expanded graphite material.
[0052] Weigh 0.3g of the prepared titanium dioxide quantum dot loaded expanded graphite material, 0.0857g of conductive carbon black, and 0.0428g of polyvinylidene fluoride, grind them thoroughly in a mortar and transfer them to a finger bottle, add 2.4mL of nitrogen methyl pyrrolidone, stir magnetically for 12h, and then use a coater to evenly coat the material on the zinc foil. Transfer to an 80℃ oven and dry for 12h. Finally, cut the obtained material into 1.2cm circular pole pieces, and use manganese oxide as the positive electrode material to form a CR2032 button battery.
[0053] Figure 1 The titanium dioxide quantum dot-loaded expanded graphite material (TiO 2 Scanning electron microscope (SEM) characterization of QDs@EG). Figure 1 It can be observed that EG is built up piece by piece like a coral reef, showing a circular feature.
[0054] Figure 2The titanium dioxide quantum dot-loaded expanded graphite material (TiO 2 Transmission electron microscopy (TEM) characterization of QDs@EG). Figure 2 It can be seen that titanium dioxide quantum dots are anchored on the surface of expanded graphite, with an average size of about 10nm.
[0055] Figure 3 The titanium dioxide quantum dot-loaded expanded graphite material (TiO 2 High-resolution transmission electron microscopy (HR-TEM) image of QDs@EG. Figure 3 It can be seen that the plane spacing of titanium dioxide quantum dots is 0.352nm, which is similar to that of anatase TiO 2 The (101) lattice plane is very consistent. At the same time, the interplanar distances of EG are measured to be 0.337nm and 0.203nm, corresponding to the (002) and (101) planes of graphite, respectively.
[0056] Figure 4 The material (TiO 2 XPS spectrum of QDs@EG). Figure 4 We can see the full spectrum of EG@TiO2 QDs, which is mainly composed of several peaks, corresponding to carbon, oxygen, and titanium elements.
[0057] Figure 5 The negative electrode protective layer (TiO 2 QDs@EG), the negative electrode protective layer with expanded graphite obtained in Comparative Example 1, and the linear scanning voltammogram of the bare zinc electrode without the protective layer. Figure 5 It can be seen that the hydrogen evolution overpotential of the negative electrode equipped with a protective layer is smaller than that of the bare zinc electrode, indicating that the protective layer effectively alleviates the hydrogen evolution side reaction.
[0058] Figure 5 The negative electrode protective layer (TiO 2 QDs@EG), the negative electrode protective layer with expanded graphite obtained in comparative example 1, and the chronoamperometry of the bare zinc electrode without the protective layer. Figure 6It can be seen that in the bare zinc electrode and EG@Zn, the current density continues to rise within 300s, showing a long and rampant two-dimensional diffusion process, in which Zn2+ tends to diffuse laterally along the surface and easily deposits at the tip to form dendrites. In sharp contrast, after the restricted two-dimensional diffusion, the long-term 3D diffusion process in ET@Zn has a stable and low current density, which can promote the uniform and flat deposition of zinc and inhibit the growth of zinc dendrites. This is in sharp contrast to the situation where Zn2+ diffuses laterally on the surface and easily deposits at the tip to form dendrites.
[0059] Figure 7 The negative electrode protective layer (TiO 2 QDs@EG) at a current of 5 mA cm -2 , with a capacity of 2.5 mAh cm -2 Cyclic performance under conditions. Figure 7 It can be seen that the cycle life of the symmetrical battery equipped with a negative electrode protective layer of titanium dioxide quantum dots loaded with expanded graphite reaches 3000h.
[0060] Figure 8 The negative electrode protective layer (TiO 2 Scanning electron microscope (SEM) characterization of a symmetric battery of QDs@EG after 100 cycles. Figure 8 It can be seen that the surface dendrite growth of the symmetrical battery equipped with a negative electrode protective layer of titanium dioxide quantum dots loaded with expanded graphite is reduced after 100 cycles, and the dendrites show horizontal growth.
[0061] Fig. 9 The negative electrode protective layer (TiO 2 The long cycle performance test diagram of the full battery composed of QDs@EG) and manganese oxide electrode. Fig. 9 It can be seen that the capacity of the full battery equipped with the negative electrode protective layer of titanium dioxide quantum dots loaded with expanded graphite is stable at 100 mAh g -1 , the Coulomb efficiency is also close to 100%.
[0062] Fig.10 The negative electrode protective layer (TiO 2 Self-discharge behavior of a full battery consisting of QDs@EG) and manganese oxide electrodes in electrolyte. Fig.10 It can be seen that the full battery equipped with a negative electrode protective layer of titanium dioxide quantum dots loaded with expanded graphite still maintains more than 90% of its capacity after being fully charged and standing for 48 hours.
[0063] Example 2
[0064] This embodiment provides a method for preparing a negative electrode protective layer (EG) loaded with expanded graphite, the preparation method comprising the following steps:
[0065] (1) Add 1 g of graphite into a beaker, and then add 8 mL of 75% sulfuric acid into the beaker. Cover the dispersion with a layer of plastic wrap and stir at room temperature for 30 min. The solution is named solution (1).
[0066] (2) 0.5 g of potassium permanganate was slowly added to solution (1), followed by a constant temperature water bath at 45°C. After the reaction for one hour, the resulting material was neutralized and placed in an oven at 80°C for drying for 12 hours.
[0067] (3) The dried product obtained in step (2) is placed in a porcelain boat, and placed in a muffle furnace at 900° C. for 30 min to obtain the final product, expanded graphite (EG).
[0068] The CR2032 button battery process is the same as that in Example 1.
[0069] Finally, it should be noted that the detailed description of the above embodiments and related drawings is only used to illustrate the technical solution of the present invention rather than to limit it. The present invention is not limited to the above-mentioned specific implementation methods. Under the guidance of the present invention, any modifications or equivalent substitutions made by those skilled in the art without departing from the purpose and scope of the present invention shall be covered within the scope protected by the claims of the present invention.
Claims
1. A method for preparing a zinc negative electrode protective layer material for an aqueous zinc ion battery, It is characterized in that The steps include: (1) dispersing the carbon material in an acidic liquid and stirring at room temperature to fully mix the carbon material to obtain a uniform suspension; (2) adding manganese salt to the mixed solution obtained in step (1), stirring at room temperature, and then placing in a constant temperature water bath; (3) washing, centrifuging, drying, and calcining the product obtained by the reaction to obtain expanded graphite; (4) uniformly dispersing the expanded graphite obtained in step (3) in a solvent, and stirring to obtain a dispersion; (5) adding the titanium-containing organic compound to the dispersion obtained in step (4) and stirring; (6) adding deionized water to the dispersion obtained in step (5) and refluxing; (7) The product obtained in step (6) is centrifuged, washed, dried and calcined to obtain a protective layer.
2. A method for preparing a zinc negative electrode protective layer material for an aqueous zinc ion battery as claimed in claim 1, It is characterized in that In step (1), the carbon material is graphite; and the acidic liquid is 50% to 80% sulfuric acid.
3. A method for preparing a zinc negative electrode protective layer material for an aqueous zinc ion battery as claimed in claim 1, It is characterized in that In step (2), the manganese salt is potassium permanganate; the stirring time is 0.5-2 hours; the constant temperature water bath time is 0.5-2 hours; and the water bath temperature is 30-100°C.
4. A method for preparing a zinc negative electrode protective layer material for an aqueous zinc ion battery as claimed in claim 1, It is characterized in that In step (3), the washing process washes the material to neutrality; the drying time is 10-14 hours, and the drying temperature is 60-100° C.; the calcination temperature is 700-1100° C.; and the calcination time is 10-60 minutes.
5. A method for preparing a zinc negative electrode protective layer material for an aqueous zinc ion battery as claimed in claim 1, It is characterized in that In step (4), the mass of expanded graphite added is 0.2-2 g / mL; the solvent is ethanol; and the stirring time is 0.1-1 hour.
6. A method for preparing a zinc negative electrode protective layer material for an aqueous zinc ion battery as claimed in claim 1, It is characterized in that In step (5), the titanium-containing organic compound is tetrabutyl titanate; the volume ratio of the titanium-containing organic compound to the ethanol dispersion is 0.5:100-1:100; and the stirring time is 0.1-1 hour.
7. A method for preparing a zinc negative electrode protective layer material for an aqueous zinc ion battery as claimed in claim 1, It is characterized in that The volume of the deionized water added in step (6) is 0.1:50 to 2:50 of the volume of the ethanol dispersion; the reflux temperature in step (6) is 60-150° C.; and the reflux time in step (6) is 4-10 hours.
8. A method for preparing a zinc negative electrode protective layer material for an aqueous zinc ion battery as claimed in claim 1, It is characterized in that In step (7), the product is centrifuged 1-5 times; the drying time is 8-16 hours; the drying temperature is 60-100°C; the calcination temperature is 300-500°C; and the calcination time is 2-6 hours.
9. A zinc negative electrode protective layer material for an aqueous zinc ion battery prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the protective layer material according to claim 9 at the zinc negative electrode interface of an aqueous zinc ion battery.
Citation Information
Patent Citations
Titanium oxide quantum dot-carbon sodium ion battery negative electrode material and preparation method thereof
CN110444749A
Zinc negative electrode with composite nanofiber protective layer as well as preparation and application of zinc negative electrode
CN113097496A
Zinc metal negative electrode with uniform nanoparticle coating as well as preparation method and application of zinc metal negative electrode
CN117334823A
Core-shell type quantum dots structured metal Cobalt oxide-nanocabon composite, cathode active material for lithium secondary battery using it and fabrication process thereof
KR1020160060378A
Cited By
Aqueous zinc ion battery and preparation and application of modified zinc negative electrode of aqueous zinc ion battery
CN119833526A
Preparation and application of aqueous zinc-ion battery and modified zinc anode thereof
CN119833526B
Titanium dioxide negative pole piece, preparation method thereof and aqueous lithium ion battery
CN121790280A
Titanium dioxide negative electrode sheet, preparation method thereof and aqueous lithium ion battery
CN121790280B
